The emerging roles of protein arginine methyltransferases in antiviral innate immune signaling pathways - Nie, Hui; Li, Qingchao; Pan, Wei (Frontiers in Microbiology, 2023)
The Protein Arginine Methyltransferases (PRMTs) family is involved in various biological processes, including gene transcription, pre-mRNA splicing, mRNA translation, and protein stability. Recently, mounting evidence has shown that PRMTs also play critical roles in regulating the host antiviral immune response, either in an enzymatic activity dependent or independent manner. This review aims to provide an overview of the recent findings regarding the function and regulatory mechanisms of PRMTs in the antiviral response. These findings have the potential to aid in the discovery and design of novel therapeutic strategies for viral infections.